Pengaruh Kepemimpinan Transformasional Terhadap Employee Engagement dengan Dimediasi oleh Budaya Kerja dan Kepuasan Kerja Sebagai Variabel Intervening - Ibrahim, Amrin; Wibowo, Imam; Latukismo, Tatag Herbayu (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the direct and indirect effects of Transformational Leadership on Employee Engagement, with Organizational Culture and Job Satisfaction as mediating variables. Conducted within a military organizational context—specifically at Denma Mabes AD—the research involved 75 respondents. A quantitative approach using path analysis was employed. The findings reveal that Transformational Leadership has a significant direct influence on Employee Engagement, Organizational Culture, and Job Satisfaction. Furthermore, both Organizational Culture and Job Satisfaction have significant direct effects on Employee Engagement. Importantly, both mediating variables were found to significantly mediate the relationship between Transformational Leadership and Employee Engagement. These results underscore the strategic role of leadership that is inspirational, empowering, and individually considerate in shaping a supportive and satisfying work environment, which in turn enhances employees' emotional and professional engagement. The practical implication of this study highlights the need to strengthen leadership capacity and foster a positive work culture to boost personnel engagement and, ultimately, improve organizational performance